TRANSLANGUAGING TECHNIQUES IMPLEMENTED BY LECTURERS IN MULTILINGUAL ELT CLASSROOM: A CASE STUDY - Gelong, Marseli Yulianti Uba Puhu; Daniel Ari Widhiatama (Bajang Institute, 2024)
This research aims to explore the implementation of translanguaging techniques in teaching English in multilingual classes at Universitas Mercu Buana Yogyakarta, with the aim of understanding the implementation of translanguaging technique, types of translanguaging technique used by lecturer as well as the role of supporting technology. This qualitative case study involves two PBI lecturers who teach Cross-Cultural Understanding and Drama courses to students from Indonesia, Kyrgyzstan, and Turkmenistan. Data was collected through classroom observations, interviews, and data analysis. The research results show that the application of translanguaging techniques carried out by lecturers to explain material by combining English, Indonesian and Kyrgyz makes students more actively participate and understand the material in the learning process. Apart from that, it was also found that the translanguaging technique that was most widely used by lecturers was inter-sentential translanguaging with 15 appearances, followed by intra-sentential translanguaging 3 times and tag translanguaging 2 times. In addition, technology such as Google Image, YouTube, and Google Translate supports the application of translanguaging techniques and makes lessons more effective and interesting.